Giving Active Breaks and Snack Reduced Fatigue and Improved Motivation of Work And Productivity of Jaja Gipang Employee - Devi, Mia Lestari; Indah Sri Handari Adiputra, Luh Made; Sutajaya, I Made (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2020)
The production of jaja gipang to packaging is done manually. Jaja gipang employee do monotonous work for a long time approximately four hours of work and are accompanied by heat exposure of approximately 29.10C. Providing active rest and snacks in a participatory manner is very much needed. This study aims to prove and apply active resting and snacking to reduce fatigue and increase work motivation and productivity of jaja gipang employees in Sading village. This research is quasi-experimental using treatment by subject design and pre and posttest group design patterns, carried out an assessment in the form of: (a) giving active breaks and snacks to reduce fatigue jaja gipang employees measured using a 30 Items questionnaire of Rating Scale; (b) the provision of active breaks and snacks increases the work motivation of jaja gipang employees recorded with work motivation questionnaires; (c) giving active breaks and snacks increases the productivity recorded based on the output (the product produced) divided by the input (pulse) multiplied by time. Data collection was carried out before and after work in Period I and Period II of 13 samples for 10 (ten) days. The data obtained were analyzed by t-paired test at a significance level of 5%. The results showed that giving snacks and active breaks reduced fatigue by 27.27%, increased work motivation by 28.20%, and increased the productivity of jaja gipang employee by 23.31%. The conclusion is the provision of active breaks and snacks can reduce fatigue and increase work motivation and productivity of jaja gipang employee.